Teaching through multi-user virtual environments : applying dynamic elements to the modern classroom - Vincenti, Giovanni; Braman, James, 1981- (Hershey, PA : Information Science Reference, 2011)
'This book is a must-read for all educators and practitioners, of any subject and at any level, who wish to incorporate a dynamic online element to their classroom'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Educational technology -- United States; Computer-assisted instruction -- United States; Teachers -- Effect of technological innovations on -- United States; Distance education